Hepatitis B prevalence and incidence in the fishing communities of Lake Victoria, Uganda: a retrospective cohort study - Paul Kato Kitandwe; Enoch Muyanja; Teddy Nakaweesa; Annet Nanvubya; Ali Ssetaala; Juliet Mpendo; Brenda Okech; Bernard S. Bagaya; Noah Kiwanuka; Matt A. Price (BMC, 2021)
Abstract Introduction Hepatitis B is a serious potentially fatal hepatocellular disease caused by the hepatitis B virus. In the fishing communities of Lake Victoria Uganda, the hepatitis B virus infection burden is largely unknown. This study assessed the prevalence and incidence of hepatitis B in these communities. Methods This was a retrospective cohort study that tested serum samples collected from 13 to 49-year-old study participants that were residing in two Ugandan Lake Victoria fishing communities of Kasenyi (a mainland) and Jaana (an island). The samples were collected between 2013 and 2015 during the conduct of an HIV epidemiological cohort study in these communities. A total of 467 twelve-month follow-up and 50 baseline visit samples of participants lost to follow-up were tested for hepatitis B serological markers to determine prevalence. To determine hepatitis B virus incidence, samples that were hepatitis B positive at the follow-up visit had their baseline samples tested to identify hepatitis B negative samples whose corresponding follow-up samples were thus incident cases. Results The baseline mean age of the 517 study participants was 31.1 (SD ± 8.4) years, 278 (53.8%) of whom were females. A total of 36 (7%) study participants had hepatitis B virus infection, 22 (61.1%) of whom were male. Jaana had a higher hepatitis B virus prevalence compared to Kasenyi (10.2% vs 4.0%). In total, 210 (40.6%) study participants had evidence of prior hepatitis B virus infection while 48.6% had never been infected or vaccinated against this disease. A total of 20 (3.9%) participants had results suggestive of prior hepatitis B vaccination. Hepatitis B incidence was 10.5 cases/100PY (95% CI: 7.09-15.53). Being above 25 years of age and staying in Jaana were significant risk factors for hepatitis B virus acquisition (AOR 1.6, 95% CI: 1.1-2.2; p < 0.01 and 1.4, 95% CI: 1.1-1.8; p < 0.01 respectively). Conclusion Hepatitis B virus incidence in Lake Victoria fishing communities of Uganda is very high, particularly in the islands. Interventions to lower hepatitis B virus transmission in these communities are urgently needed.